Der Aufstieg des Normalarbeitsverhältnisses in Deutschland: Vom Ausbruch des Zweiten Weltkriegs bis zur Ölkrise 1973 - Michael J. Kendzia (Institute for the Study of Labor (IZA), 2010)
– This article provides a historical overview of the institutional development of the structural elements of the standard employment relationship from the beginning of World War II until the 1973 oil crisis. The analysis deals with the determining factors of the reconstitution and adjustment of these elements during that time. For this purpose, the interests of the actors involved are displayed. The historical analysis finds that the standard employment relationship attained its essential stature already prior to the pension reform of 1957. The preliminary peak of the institutional arrangement of the standard employment relationship was reached during the era of Chancellor Brandt in the beginning of the 1970s.
Keywords: J50; J40; 330; Normalarbeitsverhältnis; Beschäftigungsmodell; Lohnarbeitsverhältnis; Sozialpolitik; Sozialversicherungssystem